Vaccine anxieties, vaccine preparedness: Perspectives from Africa in a Covid-19 era. (April 2022) - Leach, Melissa; MacGregor, Hayley; Akello, Grace; Babawo, Lawrence; Baluku, Moses; Desclaux, Alice; Grant, Catherine; Kamara, Foday; Nyakoi, Marion; Parker, Melissa; Richards, Paul; Mokuwa, Esther; et al.
Abstract: Global debates about vaccines as a key element of pandemic response and future preparedness in the era of Covid-19 currently focus on questions of supply, with attention to global injustice in vaccine distribution and African countries as rightful beneficiaries of international de-regulation and financing initiatives such as COVAX. At the same time, vaccine demand and uptake are seen to be threatened by hesitancy, often attributed to an increasingly globalised anti-vaxx movement and its propagation of misinformation and conspiracy, now reaching African populations through a social media 'infodemic'. Underplayed in these debates are the socio-political contexts through which vaccine technologies enter and are interpreted within African settings, and the crucial intersections between supply and demand. We explore these through a 'vaccine anxieties' framework attending to both desires for and worries about vaccines, as shaped by bodily, societal and wider political understandings and experiences. This provides an analytical lens to organise and interpret ethnographic and narrative accounts in local and national settings in Uganda and Sierra Leone, and their (dis)connections with global debates and geopolitics. In considering the socially-embedded reasons why people want or do not want Covid-19 vaccines, and how this intersects with the dynamics of vaccine supply, access and distribution in rapidly-unfolding epidemic situations, we bring new, expanded insights into debates about vaccine confidence and vaccine preparedness. Highlights: Discourses of vaccine hesitancy misrepresent African publics as ignorant or confused. Covid-19 vaccine anxieties make sense given disease, social and political experiences. Vaccine supply inequities interplay with uptake in dynamics across scales. Growing familiarity with Covid-19 vaccines has eroded worries, but not linearly. Vaccine preparedness must address health system structures and politics.